The prevalence of eustachian tube dysfunction symptoms in temporomandibular joint disorder patients. (2nd July 2019) - Newman, Alan C.; Omrani, Katayoun; Higgins, Thomas S.; Ting, Jonathan Y.; Walgama, Evan S.; Wu, Arthur W.
Abstract : Objectives/Hypothesis: Ear fullness and pressure is a common complaint seen in otolaryngology clinics and frequently is attributed to eustachian tube dysfunction (ETD). In addition to traditional tympanometry and physical examination, the seven‐item Eustachian Tube Dysfunction Questionnaire (ETDQ‐7) has recently been used to aid in the diagnosis of ETD and to assess its severity. Temporomandibular joint disorder (TMJD) is a common condition that causes similar symptoms to ETD and has been recognized as a potential confounding condition in patients presenting with ETD symptoms. We sought to determine the cross‐sectional prevalence of ETD symptoms in patients with TMJD using the ETDQ‐7. Study Design: Prospective cross‐sectional analysis. Methods: An analysis was performed of ETDQ‐7 scores in patients diagnosed with TMJD. Results: A total of 21 patients with confirmed TMJD completed the ETDQ‐7 at routine consult or follow‐up for their TMJD. The mean ± standard deviation ETDQ‐7 score for the cohort was 24.5 ± 12.5. Two‐thirds of patients had an ETDQ‐7 score of >14.5, which has been used in the literature to denote clinically significant ETD. No single question was scored significantly higher than the others. Conclusions: Symptoms of ETD are highly prevalent among patients with TMJD determined by patient‐reported outcome measures. It is not clear if these symptoms reflect true derangement of eustachian tube function in these patients or whether there is only clinical similarity between ETD and TMJD. However, future research efforts may resolve this dilemma. Level of Evidence: 4 Laryngoscope, 130:E233–E236, 2020